2021
DOI: 10.3390/sports9120172
|View full text |Cite
|
Sign up to set email alerts
|

Turbans vs. Helmets: A Systematic Narrative Review of the Literature on Head Injuries and Impact Loci of Cranial Trauma in Several Recreational Outdoor Sports

Abstract: When in public, faith-based mandates require practising Sikh men to wear a turban which may not be covered by hats or caps. This makes it impossible for practising Sikhs to wear helmets and other protective headwear, mandatory in many countries and facilities for engagement in recreational pursuits (e.g., skiing) and on adventure outdoor recreation camps mandatorily run for school groups. The result is often social exclusion and ostracisation in the case of school children. Despite studies into the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 105 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…Scholars also use the clustering method to estimate the spatial distribution and management of public facilities and reduce the dispersion of sport resources [ 6 ]. However, when monitoring the resources of public sport facilities, it is found that the calculation accuracy of the spatial spectrum estimation method is negatively correlated with the amount of information and data, which cannot meet the accuracy requirements of public sport facilities resource management and increase the occupation rate of public resources [ 7 ]. Some scholars combined the k-clustering method with the spatial spectrum estimation method to analyze the allocation and management factors and found that this method can improve the resource allocation and management level of public sport facilities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars also use the clustering method to estimate the spatial distribution and management of public facilities and reduce the dispersion of sport resources [ 6 ]. However, when monitoring the resources of public sport facilities, it is found that the calculation accuracy of the spatial spectrum estimation method is negatively correlated with the amount of information and data, which cannot meet the accuracy requirements of public sport facilities resource management and increase the occupation rate of public resources [ 7 ]. Some scholars combined the k-clustering method with the spatial spectrum estimation method to analyze the allocation and management factors and found that this method can improve the resource allocation and management level of public sport facilities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%